(3QDjI eSJbHdjIs - (3QGhjI MSf(B, (3eMeOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2001)
(3JTZjd GdefXe(B- (3JOQjH hJfejI GdGaQGO(B- (3JYhjVGJ GdGaQGO(B- (3HYV GdEJLGgGJ GdMOjKI aj eLGd EOGQI GdehGQO(B.s
Keywords: (3EOGQI GdCaQGOs; (3EOGQI GdehGQO GdHTQjIs; (3GdehGQO GdHTQjIs